Broken relationships: De-risking by correspondent banks and international trade - Lea Borchert; Ralph de Haas; Karolin Kirschenmann; Alison Schultz (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We study how terminated correspondent banking relationships affect international trade. Drawing on firm-level export data from emerging Europe, we show that when local banks lose access to correspondent services, their corporate clients experience significant export declines. This trade contraction occurs on both the extensive margin, with fewer firms exporting, and the intensive margin, with existing exporters shipping lower values. Firms only partially offset lost exports with higher domestic sales, resulting in lower total revenues and employment. Other firms cease operations entirely. These firmlevel impacts aggregate to lower industry-level exports in countries more exposed to correspondent bank retrenchment.
urn:nbn:fi-fe2024101680576
Keywords: F14; F15; F36; G21; G28; L14; 330; Correspondent banking; trade finance; de-risking; global banks; international trade; anti-money laundering